Evaluating Stock Performance: Insights from CAPM and Fama-French Models - Wang, Zhongqian (Transactions on Economics, Business and Management Research, 2024)
This study compares the Capital Asset Pricing Model (CAPM) and the Fama-French three-factor model (FF3) in predicting stock returns. The study uses historical data from three comparable companies in the technology field to analyze the strengths and limitations of the two models in real-world Settings. In total, this study consisted of 750 experiments. The technology sector was chosen because its dynamic nature and significant impact on financial markets made it an ideal candidate for this type of analysis. Excel is a very good tool for comparison of experimental data, and this study uses its calculation methods. After a careful study in the field, including regression statistics and coefficient table data analysis, research regression model data in Excel were compared. Moreover, three groups of R Square data that could be compared were obtained. Through analysis, this study obtains a fact that Fama French model has found processes a higher accuracy. This study suggests that while CAPM offers a more straightforward method for estimating expected returns, the FF3 provides a more comprehensive and more accurate cognation by an increase of size and value factors.